До питання про еволюцію міфологічних поглядів слов’ян у І тис. до н. е. - Козак, Д.Н.; Козак, H.С. (Археологія, 1995)
У публікації порівнюються дві видатні пам’ятки духовної культури давніх слов'ян — окуття піхов меча з Гринева рубежу ери і Збручанський ідол кінця І тис. н. е. Публикуемые памятники отражают мифологические воззрения древних славян на разных этапах социально-экономического и духовного развития.
Эволюция этих воззрений касалась прежде всего представлений о пространстве и месте человека в окружающим мире.
На рубеже эры у славян господствовало представление о существовании нескольких однородных частей пространства в которых происходили события с антропо- и зооморфными героями. Герой (человек-вождь, царь, старейшина и пр.) составлял чувственно-конкретный образ мира данной группы людей, в котором природное и общественное, индивидуальное и коллективное составляли единое целое.
В Збручанском идоле — памятнике конца I тыс., все герои уже антропоморфны. Основная идея "наивной" мифологии рубежа эры — превращение героем хаоса в космос, чужда системе его образов. Мир в понимании людей уже антропоцентрический. Збручанскому идолу свойственна строго вертикальная и четко иерархическая композиция. Величина ярусов подчеркивает значимость не только тех или иных персонажей, но и важность частей пространства. Наименее значимы здесь персонажи среднего яруса — люди в ритуальном хороводе. The findings published show mythological views of the ancient Slavs at different stages of their socio-economic and intellectual development. Evolution of the views concerned first of all ideas about the space and place of man in the world which surrounded him. At the end of the epoch the Slavs had a dominating views about existence of several homogeneous parts of the space where certain events had- happened with anthropo- and zoomorphous heroes. A hero (man-leader, tsar, the elder, and so on) represented a sensitive-concrete image of a world for a group of people. The natural and the social, the individual and the collective made the single whole in that would.
In the Zbruchanian idol, a relic of the late 1st millennium, all heroes had already been anthropomorphous. The main idea of «naive* mythology which existed at the end of the epoch, namely, transformation of the chaos into cosmic space by a hero, is alien to the system of Zbruchanian idol is distinguished for its strictly vertical and distinctly hierarchical composition. The size of stages emphasizes not only meaningfulness of certain images but also importance of parts of the space. The less meaningful images there are depicted, at the mid stage: people in a ritual round dance.